1987
DOI: 10.1002/jmv.1890230413
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of low doses of hepatitis B vaccine in children: A study in 650 New Zealand children

Abstract: Six hundred and fifty New Zealand children from 2-12 years of age were vaccinated three times with 2 mcg intramuscular (IM) doses of Merck Sharp and Dohme plasma-derived hepatitis B vaccine (H-B-Vax), at 0, 1, and 6 months, and tested 2-3 months later for antibody to hepatitis B surface antigen (anti-HBs) by radioimmunoassay (RIA). Overall, 96.5% of the children seroconverted for anti-HBs by RIA, having levels greater than 2.1 RIA S/N units, with 91.2% having values greater than 10 S/N units. Anti-HBs levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In that study of 704 children who were given HBV vaccine at birth, it was shown that 96.7% of 1-to 4-year-old children had detectable anti-HBs, compared to 91% of 5-to 9-year-old children and 81% of 10-to 14-year-old children [12] . In another study, 66% of children aged 5-9 years had antibody titers above 50 IU/ml [13] .…”
Section: Discussionmentioning
confidence: 99%
“…In that study of 704 children who were given HBV vaccine at birth, it was shown that 96.7% of 1-to 4-year-old children had detectable anti-HBs, compared to 91% of 5-to 9-year-old children and 81% of 10-to 14-year-old children [12] . In another study, 66% of children aged 5-9 years had antibody titers above 50 IU/ml [13] .…”
Section: Discussionmentioning
confidence: 99%